Improving the composability of Department of Defense models and simulations - Davis, Paul K., 1943-; Anderson, Robert H. (Robert Helms), 1939-; National Defense Research Institute (U.S.). Acquisition and Technology Policy Center; Rand Corporation; United States. Department of Defense. Office of the Secretary of Defense (Santa Monica, CA : RAND, 2003)
This monograph investigates actions that could be taken by the Department of Defense (DoD) to improve the composability of its future models and simulations.In modeling and simulation, composability is the capability to select and assemble components in various combinations to satisfy specific user requirements meaningfully. Factors that determine what can be composed and the expense and risk of composing various components are examined, and many suggestions are presented on both policies and investments that would enhance prospects for composability. It is concluded that DoD must recognize that models are different from general software components and that model composability needs to be based not simply on software practice, but on the emerging science of modeling and simulation. DoD should also develop and communicate a set of realistic images and expectations, back away from excessive promises, and approach improvement measures as a "system problem" involving actions and investments in multiple areas ranging from science and technology to education and training.
"National Defense Research Institute."
Includes bibliographical references (p. 133-139).
Also available on the internet via WWW in PDF format.
Keywords: Combat -- Mathematical models; Computer simulation -- Military aspects; Military art and science -- Mathematical models